La situación de las prisiones y los centros de menores en España: Analizando las observaciones del CPT - Rogan, Mary; Aizpurua, Eva (My University, 2019)
The European Committee for the Prevention of Torture (CPT) is responsible for evaluating the treatment of persons deprived of their freedom in the 47 member States of the Council of Europe. To do so it visits detention facilities and issues reports containing its conclusions, and requests detailed responses from the States. This work analyses the content of the report produced by this organisation as a result of its visit to Spain (2016) and the response issued by the Spanish authorities. Specifically, the deficiencies identified at both the adult and juvenile detention centres are described and grouped thematically, and the degree of compliance with the recommendations is evaluated. Finally, the results and their implications are discussed.
PUBLISHED
Keywords: Places of detention; Oversight mechanisms; International bodies; Human rights; Criminal law